Unexpected Ileal Perforation in A Neonate with Anorectal Malformation: A Rare Case Report - Nurmasithah; Nisa Alyananda Ritonga; Hermanto; Sonia Edna Rumondang; Hartomarasiddin (Jurnal Ilmu Multidisiplin, 2026)
Intestinal perforation in neonates with anorectal malformations (ARM) is rare but associated with high mortality. This report presents a rare case of ileal perforation in ARM of ileal perforation associated with ARM. A 4-day-old female neonate presented with abdominal distention, fever, and failure to pass meconium; babygram examination showed only meteorism without signs of pneumoperitoneum. Exploratory laparotomy revealed ileal perforation with meconium leakage, followed by resection and anastomosis, along with the creation of a sigmoid loop colostomy with a plan for subsequent anoplasty. Despite surgical intervention, the patient unfortunately died on the third postoperative day due to sepsis. Bowel perforation is a known complication of ARM and may arise from vascular or congenital causes; the ileum, being thinner than the colon, is less able to tolerate increased intraluminal pressure, and perforation can occur even in the absence of pneumoperitoneum, with anterior abdominal wall edema serving as an important clinical clue. Although ileal perforation in ARM is extremely uncommon, early recognition of this potential complication is essential to prevent deterioration and reduce mortality in affected neonates.